Natural Course of Solar and Laser-Associated Retinal and Macular Injuries at a Primary Care Hospital in Switzerland - Wiest, Maximilian Robert Justus; Gunzinger, Jeanne Martine; Hamann, Timothy; Fasler, Katrin; Said, Sadiq; Bajka, Anahita; Muth, Daniel Rudolf; Barthelmes, Daniel; Blaser, Frank; Zweifel, Sandrine Anne (Klinische Monatsblätter für Augenheilkunde, 2023)
Background Solar and laser-associated retinopathies are rare occurrences. The two retinopathies are both photo-induced but differ in the involved intensity and duration of exposure. The purpose of this study was to evaluate the clinical features and natural course of these two entities, with a focus on the changes in the outer retina over time.Patients and Methods This retrospective analysis assessed patients with solar or laser maculopathy seen at the Department of Ophthalmology of the University Hospital Zurich in Switzerland over the last 10 years. Visual acuity (VA; Snellen) and optical coherence tomography (OCT) findings were reviewed and analyzed at baseline and last follow-up visit. Areas of damaged outer retina, identified on en face OCT images as hyporeflective areas, were tagged and compared between visits. Descriptive analysis was performed by calculating mean values ± standard deviation (SD). Statistical evaluation was done using the Wilcoxon signed rank test. A p value < 0.05 was considered statistically significant.Results Five patients with solar retinopathy and six patients with laser-associated retinopathy were identified. In the solar retinopathy group, mean VA at baseline was 0.80 (SD ± 0.37) and improved to 0.90 (SD ± 0.36). This was not statistically significant (p = 0.066). In the laser-associated retinopathy group, mean VA at baseline was 0.89 (SD ± 0.18) and improved to 1.03 (SD ± 0.09), which was not statistically significant either (p = 0.063). At baseline, in OCT cross-sections, initial changes were observed in the interdigitation, myoid, and ellipsoid zone, as well as the outer nuclear layer and the Henle fiber layer. At follow-up, most cases presented an alteration in the residual ellipsoid zone, with the degree of the aforementioned alterations depending on the size of the initial defect. A decrease of the hyporeflective alterations measured in en face OCT scans was observed in both groups but was only statistically significant in the laser-associated retinopathy group (p = 0.018 versus p = 0.172).Conclusions OCT can help to detect and monitor solar and laser-associated retinal injuries. Most injuries are minor, with good functional restitution. Minor changes in the ellipsoid zone often persist, even in cases with full visual recovery.
Keywords: retina; solar; laser; retinopathy; optical coherence tomography